2002
DOI: 10.1038/sj.onc.1205890
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation and hypermethylation of DNA in Wilms tumors

Abstract: We quantitatively analysed hypermethylation at CpG islands in the 5' ends of 12 genes and one non-CpG island 5' region (MTHFR) in 31 Wilms tumors. We also determined their global genomic 5-methylcytosine content. Compared with various normal postnatal tissues, *40 -90% of these pediatric kidney cancers were hypermethylated in four of the genes, MCJ, RASSF1A, TNFRSF12 and CALCA as determined by a quantitative bisulfite-based assay (MethyLight). Interestingly, the non-CpG island 5' region of MTHFR was less methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
123
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 32 publications
11
123
1
Order By: Relevance
“…We demonstrate hypermethylation of the MCJ intronic CpG island 16,17 26 and >50% of ovarian cancers; 16,17 however, MCJ hypermethylation has not been investigated in other tumour types. Our observations of MCJ hypermethylation in medulloblastomas, stPNETs and ependymomas suggest that MCJ inactivation plays a role in the development of a range of CNS tumour types, and this role now requires further investigation and clarification.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We demonstrate hypermethylation of the MCJ intronic CpG island 16,17 26 and >50% of ovarian cancers; 16,17 however, MCJ hypermethylation has not been investigated in other tumour types. Our observations of MCJ hypermethylation in medulloblastomas, stPNETs and ependymomas suggest that MCJ inactivation plays a role in the development of a range of CNS tumour types, and this role now requires further investigation and clarification.…”
Section: Discussionmentioning
confidence: 74%
“…Tumourspecific methylation of MCJ has also been reported in Wilms' tumours; 26 however, this is in contrast to ovarian cancers, where MCJ methylation is also a feature of the normal ovarian epithelium. 17 Strathdee et al 17 reported that the MCJ CpG island is methylated and the gene is not expressed in cells of epithelial origin but is unmethylated and expressed in cells of lymphocytic or fibroblast origin.…”
Section: Discussionmentioning
confidence: 96%
“…The overall m 5 C content of the DNA was determined by high performance liquid chromatography (HPLC) 24 on heat-denatured DNA digested with nuclease P1 and bacterial alkaline phosphatase for 2 h at 37˚C each.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we found, that a much higher percentage of Wilms tumors exhibited hypomethylation of Sat2 than pericentromeric rearrangements in Sat2 DNA-rich chromosomes as determined by karyotype analysis. 14 Because the high frequencies of cancer-linked satellite DNA hypomethylation are not positively associated with cancer-linked CpG island hypermethylation of tumor suppressor genes 8,24 (Laird P, Dubeau L, Ehrlich M, unpublished data), this hypomethylation is not likely to be just a byproduct of or preliminary to CpG island hypermethylation. These findings suggest that there are other ways by which cancer-linked satellite DNA hypomethylation contributes to oncogenesis besides favoring karyotypic instability, e.g., possibly by influencing gene expression in trans.…”
mentioning
confidence: 99%
“…Hence, DNhpom agents might promote neoplasia in prospective tumour cells simultaneously with reactivation of HbF gene expression in erythrocytes precursors, residing inside the tumour tissues or in haematopoietic tissues of the same organism. This hypothesis is not impaired by the evidence for inactivation of tumour suppressing genes by DNA hypermethylation, since hypermethylation is specific for unique genomic sites while at the same time global DNA is hypomethylated (Ehrlich et al, 2002;Brothman et al, 2005;Ehrlich, 2005). By that ambiguity, the use of DNA demethylating agents as therapeutic anticancer regiment might contribute to carcinogenesis (Ehrlich, 2005).…”
mentioning
confidence: 99%